2023
DOI: 10.3390/ijms24076443
|View full text |Cite
|
Sign up to set email alerts
|

Sex Difference in Cardioprotection against Acute Myocardial Infarction in MAO-B Knockout Mice In Vivo

Abstract: The cardiomyocyte-specific knockout (KO) of monoamine oxidase (MAO)-B, an enzyme involved in the formation of reactive oxygen species (ROS), reduced myocardial ischemia/reperfusion (I/R) injury in vitro. Because sex hormones have a strong impact on MAO metabolic pathways, we analyzed the myocardial infarct size (IS) following I/R in female and male MAO-B KO mice in vivo. Method and Results: To induce the deletion of MAO-B, MAO-B KO mice (Myh6 Cre+/MAO-Bfl/fl) and wild-type (WT, Cre-negative MAO-Bfl/fl litterma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Histamine co-localizes with norepinephrine in neurons [ 389 ] and is enclosed in cytoplasmic granules of mast cells, which lie adjacent to blood vessels and between cardiomyocytes [ 390 ], and mast cell degranulation might occur under stress conditions [ 391 ]. Activation of MAO contributed to development of endothelial dysfunction [ 392 ] and irreversible cardiomyocyte injury in vitro [ 393 ] and in vivo [ 394 ], also the latter was restricted to males only.…”
Section: Pathophysiological Mechanisms Of Noise Exposurementioning
confidence: 99%
“…Histamine co-localizes with norepinephrine in neurons [ 389 ] and is enclosed in cytoplasmic granules of mast cells, which lie adjacent to blood vessels and between cardiomyocytes [ 390 ], and mast cell degranulation might occur under stress conditions [ 391 ]. Activation of MAO contributed to development of endothelial dysfunction [ 392 ] and irreversible cardiomyocyte injury in vitro [ 393 ] and in vivo [ 394 ], also the latter was restricted to males only.…”
Section: Pathophysiological Mechanisms Of Noise Exposurementioning
confidence: 99%
“…More recently, cardiac-specific and tamoxifen-inducible MAO-B knockout mouse has been generated and also shown to present smaller infarct size following ischemia/reperfusion injury [ 21 ]. Moreover, the lack of MAO-B in mouse cardiomyocytes reduced the infarct size in male mice, whereas it remained ineffective in female mice [ 22 ]. Further studies are necessary to fully understand how cardiomyocyte MAO-B modulates signaling pathways underlying cardioprotection in male vs female mice.…”
Section: Mao Involvement In Cardiac Pathologymentioning
confidence: 99%
“…A permanent cardiomyocyte-specific knockout of MAO-A reduces the incidence of catecholamine-induced arrhythmias in mice [ 26 ]. Recently, we demonstrated that a lack of cardiomyocyte-specific MAO-B reduces left ventricular infarct size in vitro [ 27 ] and in vivo [ 28 ]. Information on the importance of cardiomyocyte-specific MAOs in RV disease is absent.…”
Section: Introductionmentioning
confidence: 99%